The Role of Midwives in the First Level Of Health Care System - Salsa Cortizo, María Victoria (2015)
Since the beginning of human history the process of childbirth has been acknowledged as a life event involving bio-physiological as well as socio-cultured and psychological aspects. All cultures throughout history have had strategies to assist and accompany women during labor and birth, being the image of a midwife present in current and past societies. In Argentina, as in many countries of Latin America, the official discourses assign on midwifery a key role in primary health care. However, the absence of midwifes in the first level of health care leaves pregnancy, labor and postpartum controls under other professionals or under a hospital level care. In this paper we mention some successful experiences that were able to reduce maternal and child risk indicators only through the inclusion of midwives in the primary care health staff. The profile and attitude of midwife’s care during pregnancy, delivery and assistance of pregnant women during gestational period cannot be replaced by other professionals.